The “appearing” and “disappearing” ascites in the treatment of colorectal cancer: a case report - Cui, Hong-Ming; Shu, Xin-Peng; Wei, Zheng-Qiang; Wu, Xing-Ye (Frontiers in Oncology, 2024)
Background Colorectal cancer (CRC) is one of the most common cancers worldwide. In the treatment of CRC patients, oxaliplatin plays a pivotal role with moderate side effect. Neurotoxicity, myelosuppression, ototoxicity, delayed hypersensitivity reactions, and rhabdomyolysis induced by oxaliplatin have been reported individually. However, the occurrence of oxaliplatin-induced ascites has not been reported in the past. Case Description We reported a case of rare ascites in a patient diagnosed with upper rectal cancer and treated with radical surgery plus postoperative chemotherapy using oxaliplatin. Conclusions This case suggested that chemotherapy with oxaliplatin might cause ascites. When CRC patients who underwent chemotherapy with oxaliplatin developed ascites, surgeons should actively determine whether it was caused by chemotherapy side effects or tumor recurrence to avoid unnecessary surgery.